2004
DOI: 10.1038/sj.bmt.1704476
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immunity to measles, mumps and rubella after MMR vaccination among children with bone marrow transplants

Abstract: Summary:Measles, mumps and rubella (MMR) vaccine-induced long-term immunity was studied in 30 children with bone marrow transplants (BMT). Immunity at baseline for MMR was 13.3, 33.3 and 66.6%, respectively. MMR vaccination failed to induce adequate and persistent responses to measles and mumps; seropositivity at 1 and 12 months for measles was 26.6 and 23.3% and for mumps 46.6 and 36.6%, respectively. In contrast, 27 of 30 children with a BMT were immune to rubella 1 month after immunization and retained prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 13 publications
4
18
1
Order By: Relevance
“…Long-term immunity was shown by the protection of treated hosts against tumor rechallenge, increased numbers of memory T cells, and significantly elevated serum levels of both IFNg and IL-10. In addition, it is well accepted that serum antibody levels and its persistence are responsible for the establishment of long-term immunity (23)(24)(25). We observed in this study an enhanced tumorassociated antibody response induced by T-cell + IL-2 + IL-21 therapy, and the use of B-cell-deficient mice provided direct evidence that humoral responses truly contribute to T-cell + IL-2 + IL-21-elicited antitumor immunity.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Long-term immunity was shown by the protection of treated hosts against tumor rechallenge, increased numbers of memory T cells, and significantly elevated serum levels of both IFNg and IL-10. In addition, it is well accepted that serum antibody levels and its persistence are responsible for the establishment of long-term immunity (23)(24)(25). We observed in this study an enhanced tumorassociated antibody response induced by T-cell + IL-2 + IL-21 therapy, and the use of B-cell-deficient mice provided direct evidence that humoral responses truly contribute to T-cell + IL-2 + IL-21-elicited antitumor immunity.…”
Section: Discussionsupporting
confidence: 56%
“…Lack of induction of systemic and longterm antitumor immunity is one of the obstacles to the achievement of successful cancer immunotherapy. It is well accepted that antibody production and its persistence can promote the retention of long-term immunity (23)(24)(25). Therefore, any new reagent that can serve as an effective immune adjuvant to adoptively transferred T cells by boosting both cellular and humoral antitumor immunity represents a novel approach for human cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reasons for the higher percentage found in our study are the following: (1) In the first group, the majority of patients received autologous HSCT, and it has been reported that the loss of specific Ab is higher after allogeneic HSCT than after autologous, and all the patients in our study group received allogeneic HSCT. 12 (2) In both studies, the follow-up time was shorter than that in this report. Godoi et al reported that the loss of HAV Ab was significantly associated with a longer follow-up, and the probability of loss of antibodies had reached 23.4% (±9.6%) at 4 years after HSCT.…”
Section: Discussioncontrasting
confidence: 46%
“…Japanese guidelines have suggested target protective antibody titers that healthcare workers must achieve against these viruses (8). It is accepted that antibody titers decrease exponentially with time in children without exposure to circulating virus (9)(10)(11)(12). However, it remains unclear how antibody titers persist or decrease with age.…”
Section: Introductionmentioning
confidence: 99%